The gendered appropriation of the mobile phone for online health information by youths in Zimbabwean tertiary learning institutions - Tsarwe, Stanley Zvinaiye (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 2016)
The study uses domestication of technology and Cultural Studies theories to investigate how youth in three institutions of tertiary learning in Harare, Zimbabwe are accessing health-related information online using their smart phones. The study critically examines how youths deploy these digital media technologies to construct their identities in a context where social and political power is unevenly distributed. To understand these issues, the study uses a triangulated research design comprising a social survey, in-depth individual interviews and field observation for data collection. Results from this data gathering showed that the use of digital media technologies differ across gender, at least in terms of the distribution of online health seeking practices between male and female youths. According to the survey results, more women tend to use their mobile phones to access health-related information. Data from the individual in-depth interviews showed that the most significant site of social change (social disruption) relates to how digital media facilitates emerging new identities (i.e. identity in the broader sense as well as health-related and sexual health identities). For both young men and young women, mobile phones are used precisely for image management, peer acceptance and the desire to define respective feminities and masculinities within their social networks. Both male and female youths assert they are able to access a variety of information online, and some of this information would not easily accessible when sought from traditional structures such as their parents. This way, youth feel that digital media technologies allow them to cultivate their own preferred identities outside the purview of parental authority and social control. Drawing on postmodern literature, such emerging identities are predicated on cultural volatility, unpredictability, decentralisation and refusal to fixation and conformity to socially constructed identities about being a youth, or being a young Zimbabwean woman or man, for example. Thus, the use of mobile phones and mobile Internet by youths in Zimbabwe to access health-related information has sociopolitical significance, because it allows young people to fashion preferred identities that resists entrenched regimes of social power. For young people in Zimbabwe, online health seeking practices precisely reflects attempt towards negotiating with and circumvent the structural limitations of either an expensive health care system or the general curiosity associated with growing up. That way, it is arguable that youth use digital media technologies to help them exercise some level of social autonomy and agency in dealing with everyday life. Individual in-depth interviews demonstrated that mobile phones and mobile Internet can thus be seen as opening up more spaces for youth to learn more about issues about growing up, sexuality and adolescents that a conservative society such as Zimbabwe traditionally consider as 'inappropriate' for youth consumption. They argued that the inability of parents to discuss with them issues about growing up often result in them "finding out on our own" using digital media technologies to satisfy the desire to wean themselves from what they view as arbitrary and asymmetrical social power. The study demonstrated that youth use the mobile phone to challenge the social world of adults and to show resistance to it, thereby strengthening a subculture as well as constructing an identity. However, despite the positive attributes of social capital, connectivity and personalised experience afforded by the mobile phone, the mobile phone is sometimes a source of conflict in relationships between young men and women; that is, between unmarried partners. Young women reported that their boyfriends often force them to disclose who they communicate with using their mobile phones. They also reported that their boyfriends often did some random surveillance of their social media contacts and activities. Thus, whilst one of the mobile phone's most powerful attribute is its ability to offer personalised experience, as well as offer synchronised and unlimited access to distant connections, results from in-depth interviews showed that some unwritten expectations and norms dictated that young men closely watch their 'girlfriends' social media activities, including their online search activities. As a result, privacy as well as the much touted relationship between mobile phone and women's autonomy becomes contested arenas. Even at young ages, and before marriage, women are socialised to show subservience to their partners by allowing them access to their mobile phones.
Keywords: Uncatalogued